A brief review of processing techniques for NiAl intermetallic composites. (2023) - Aprajak; Jha, Pushkar; Mohapatra, S.K.; Behera, A.; Joshi, K.K.; Rahul; Hasan, Md.E.; Sinha, D.K.
Abstract: In recent decades, NiAl intermetallic compounds have become a potential candidate for elevated temperature structural materials for aerospace applications due to their exceptional properties. In-spite of having lucrative properties, one thing that restricts their application are low ductility and fracture toughness at room temperature. Several attempts have been made by the researchers to overcome these bottlenecks by adopting feasible processing routes. In this paper, an attempt has been made to highlight the various processing techniques with a view to indicate the most suitable technique for the development of NiAl intermetallic composites.